School Principals’ Strategies in Implementing Academic Supervision in Resource-Limited School: A Case Study at Public Elementary School 2 Gondangwayang - Ana Zulaikah; Eka Prestianingsih; Danial Muhamad; Soedjono Soedjono (Journal of Educational Sciences, 2026)
Improving learning quality through effective academic supervision remains a challenge for elementary schools operating in resource-limited contexts. This study aims to examine the strategies employed by a school principal in implementing academic supervision in a resource-constrained elementary school. The research was conducted at SD Negeri 2 Gondangwayang in Kedu Subdistrict, Temanggung Regency, using a qualitative descriptive approach. Data were collected through in-depth interviews, classroom observations, and document analysis involving the principal, teachers, and a school supervisor. The findings indicate that academic supervision can be implemented effectively despite limited facilities through adaptive and context-based leadership. The principal applied key strategies including efficient time management, the use of simple supervision tools, collaborative supervision practices, optimization of internal professional learning communities, empowerment of lead teachers, and continuous monitoring of instructional practices. These strategies positively influenced teachers’ professional performance, particularly in lesson planning discipline, instructional variation, and openness to reflective practice. Academically, this study contributes to instructional leadership theory by demonstrating how adaptive and collaborative supervision models operate effectively in low-resource school contexts. Practically, the findings provide guidance for school principals in similar settings to optimize supervision practices without dependence on extensive infrastructure.